2012
DOI: 10.1111/j.1538-7836.2012.04624.x
|View full text |Cite
|
Sign up to set email alerts
|

Unfractionated heparin dosing in young infants: clinical outcomes in a cohort monitored with anti‐factor Xa levels

Abstract: To cite this article: Schechter T, Finkelstein Y, Ali M, Kahr WH, Williams S, Chan AK, deVeber G, Brandã o LR. Unfractionated heparin dosing in young infants: clinical outcomes in a cohort monitored with anti-factor Xa levels. J Thromb Haemost 2012; 10: 368-74.Summary. Background: Unfractionated heparin (UFH) is a widely used anticoagulant. Current American College of Chest Physicians guidelines for infants extrapolated from adults recommend 28 U kg )1 h )1 of UFH to achieve an antifactor Xa level of 0.35-0.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 37 publications
5
53
2
Order By: Relevance
“…[42][43][44] The frequency of DVT resolution observed here is similar to that previously reported among pediatric patients with non-central nervous system venous thrombosis 45,46 and among children with arterial and venous thrombosis treated with standard anticoagulation. 47 Thrombolysis did not result in a significant difference in DVT resolution in our study. Although research conducted in adult patients has shown more favorable thrombus resolution with the use of catheter-directed thrombolysis and systemic thrombolysis, [48][49][50][51][52] the superiority of these modalities compared with standard anticoagulation in preventing UE-PTS is still unclear.…”
Section: Ue-dvtcontrasting
confidence: 42%
“…[42][43][44] The frequency of DVT resolution observed here is similar to that previously reported among pediatric patients with non-central nervous system venous thrombosis 45,46 and among children with arterial and venous thrombosis treated with standard anticoagulation. 47 Thrombolysis did not result in a significant difference in DVT resolution in our study. Although research conducted in adult patients has shown more favorable thrombus resolution with the use of catheter-directed thrombolysis and systemic thrombolysis, [48][49][50][51][52] the superiority of these modalities compared with standard anticoagulation in preventing UE-PTS is still unclear.…”
Section: Ue-dvtcontrasting
confidence: 42%
“…In a study of infants younger than 6 months of age who were treated for deep venous thrombosis with continuous UFH targeting therapeutic anti-Xa levels, many infants remained subtherapeutic despite increased UFH doses. 24 The majority of infants had thrombus regression and no recurrence, but there was an 11% risk of major bleeding. Based on these data, infants may not require increased UFH doses despite decreased UFH response based on standard laboratory tests.…”
Section: Org Frommentioning
confidence: 96%
“…Eighty-five (57%) patients were female. Overall, 78 (52%) patients were in the low-dose and 71 (48%) were in the high-dose UFH group; 94 (63%) patients were enrolled in the RCT (47 [50%] low-dose, 47 [50%] high-dose UFH), and 55 (37%) patients in the parallel cohort receiving UFH as per standard-of-care (31 [56%] low-dose, 24 [44%] highdose UFH).…”
Section: Patient Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Impact of patient age, maturity, and developmental hemostasis The coagulation system in children differs significantly from adults and evolves in an asynchronous manner with growth and maturation, 7,8 affecting the pharmacology, 9,10 clearance, 11 and safety 12 of common anticoagulants, particularly heparinoids and the effect of hemodilution with routine interventions like transfusions.…”
Section: Area Of Concern Descriptionmentioning
confidence: 99%